Peran Perilaku Cyberloafing dalam Memediasi Pengaruh Budaya Organisasi, Lingkungan Kerja dan Workplace Boredom terhadap Kinerja Pegawai PT. Geo Dipa Energi (Persero) - Reli Suhendri; Deden Mulyana; Yusuf Abdullah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the influence of organizational culture, work environment, and workplace boredom on employee performance through Cyberloafing behavior among employees at PT Geo Dipa Energi (Persero). The research employed a survey method with a quantitative descriptive approach, enabling systematic collection of numerical data to identify relationships among variables. The sample consisted of 339 employees selected purposively to reflect diverse perceptions regarding organizational culture, working conditions, and levels of boredom. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM), which allows testing both direct and indirect effects among variables. The results indicate that organizational culture, work environment, and workplace boredom significantly affect employee performance, both directly and through Cyberloafing behavior. Cyberloafing was found to mediate the relationship between organizational culture, work environment, and employee boredom with performance, thereby either strengthening or weakening the influence of these variables on work outcomes. These findings highlight the importance of managing an organizational culture that promotes productivity, improving a conducive work environment, and reducing employee boredom levels. Additionally, controlling Cyberloafing behavior is crucial for optimizing employee performance. The study provides practical implications for the management of PT Geo Dipa Energi (Persero) in designing effective policies and programs to enhance work efficiency and employee satisfaction.